KETIDAKMAMPUAN MENAFKAHI ISTERI OLEH SUAMI SEBAGAI ALASAN FASAKH NIKAH (Studi Komparatif antara Madzhab Syafi’i dan Madzab Hanafi) - Faruq, Ahmad (Irtifaq, 2020)
Abstract: This article examines how the husband's inability to provide for his wife as a reason for marriage fasakh according to Syafi’i and Hanafi. With the library research model (library research), the authors use analyzing the results using content analysis. The results showed: (1). because permissible marriage fasakh is the inability of the husband to the minimum limit of living determined by fiqh (aqalun nafaqah) both related to clothing, food, boards (2). The scope and causes of the marriage fasakh are the inability of the husband to provide a different opinion between the Shafi'i and Hanafi schools of thought. Syafi'i School of Law allows fasakhs if the wife wishes, and fasakhs are only done by judges. If the wife prefers to be patient, then the liability is categorized as debt for the husband and the wife may choose to work even if she leaves the house without her husband's permission. The Hanafi school of thought does not allow fasakh absolutely. Keywords: Inability to Support, Fasakh Nikah.